Effect of Ceria Doping on the Mechanical Properties and Phase Stability of Partially Samaria-Stabilized Zirconia Crystals - Borik, Mikhail; Chislov, Artem; Kulebyakin, Alexej; Lomonova, Elena; Milovich, Filipp; Myzina, Valentina; Pankratov, Vladimir; Poselennov, Alexandr; Ryabochkina, Polina; Sidorova, Natalia; Tabachkova, Nataliya; Zakharov, Denis; et al. (MDPI, 2024)
The effect of ceria doping of (ZrO2)1−x(Sm2O3)x crystals on their phase composition, microhardness and fracture toughness was studied. The (ZrO2)0.995−x(Sm2O3)x(CeO2)0.005 crystals (where x = 0.032, 0.037 and 0.04) were grown using directional melt crystallization in a cold crucible. The mechanical properties, such as microhardness and fracture toughness, were explored using Vickers indentation. It was shown that the (ZrO2)0.995−x(Sm2O3)x(CeO2)0.005 solid-solution crystals contained both Ce4+ and Ce3+ ions. Phase analysis data suggested that CeO2 doping increased the tetragonality degree of the transformable t phase and reduced the tetragonality degree of the non-transformable t’ phase as compared to the (ZrO2)1−x(Sm2O3)x crystals. As a result, the t→m phase transition triggered by the indentation-induced stress in the CeO2-doped crystals was more intense and covered greater regions. CeO2 doping of the solid solutions increased the fracture toughness of all the crystals studied, whereas the microhardness of the crystals changed only slightly. CeO2 doping of the (ZrO2)1−x(Sm2O3)x solid solutions in the experimental concentration range did not improve the high-temperature phase stability of the crystals and did not prevent high-temperature degradation of their fracture toughness. © 2024 by the authors. --//-- This is an open-access article Borik, M.; Chislov, A.; Kulebyakin, A.; Lomonova, E.; Milovich, F.; Myzina, V.; Pankratov, V.; Poselennov, A.; Ryabochkina, P.; Sidorova, N.; et al. Effect of Ceria Doping on the Mechanical Properties and Phase Stability of Partially Samaria-Stabilized Zirconia Crystals. Crystals 2024, 14, 736. https://doi.org/10.3390/cryst14080736 published under the CC BY 4.0 licence.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; Ce-Sm-PSZ; directional melt crystallization; fracture toughness; solid solutions; ZrO2